Assessing the Impact of Racism on Black Faculty in White Academe: A Collective Case Study of African American Female Faculty. - DADE, KAREN; TARTAKOV, CARLIE; HARGRAVE, CONNIE; LEIGH, PATRICIA (Western Journal of Black Studies)
Using a case study approach, the authors of this article strive to explore the challenges and adverse impact that faculty of color often experience due to structural inequities, institutional racism, and the lack of cultural awareness on the part of White institutions. Furthermore, the purpose of this article is to demonstrate that even when there is a significant number of faculty members of color, stereotyping and discrimination still occur and often impact the promotion, retention, and experiences of newly recruited faculty of color. Our narratives as African American female faculty are presented as a collective case study in this article. An analysis of the narratives, strategies for retention and recruitment, and validation of the collective experience through un-silencing the voices are discussed.